HUBUNGAN SIKAP IBU HAMIL TM III DENGAN PERILAKU DIET SELAMA HAMIL DI PMB YULIANA KOTA LAMONGAN - Fitriyah, Lailatul; Purwati, Anik; Retnaningsih, Reny (NHM PRESS, 2024)
As a result of non-fulfillment of energy and protein intake in pregnant women can lead to chronic energy deficiency (SEZ), where the size of the upper arm circumference (LILA) is less than 23.5 cm, pregnant women with SEZ are also at risk of giving birth to babies with low birth weight (LBW). This study aims to determine the relationship between the attitude of pregnant women TM III with dietary behavior during pregnancy in TPMB Yuliana Lamongan city. Analytical descriptive research with cross sectional approach. The study was conducted at PMB Yuliana Lamongan City in November 2023 with a population of 53 people. Sampling technique with Accidental Sampling technique and obtained a sample of 32 people. Chi square test results obtained r value of 0.023 < 0.05, which means H0 is rejected, so there is a significant relationship between the attitude of pregnant women TM IIII with dietary behavior during pregnancy in PMB Yuliana Lamongan. Based on the results of research from 32 respondents TM III pregnant women in PMB Yuliana Lamongan, statistical test results obtained by using The Chi-Square Test with SPSS determine the relationship between the attitude of TM III pregnant women with dietary behavior during pregnancy is significantly associated with the value of p-value= 0.023<0.05. So that the decision hypothesis reject H0 and accept Ha is that there is a significant relationship between the attitude of pregnant women TM III with dietary behavior during pregnancy in PMB Yuliana Lamongan.